The Prp19 complex directly functions in mitotic spindle assembly - Hofmann, Jennifer Carina; Tegha Dunghu, Justus; Dräger-Meurer, Stefanie; Will, Cindy L.; Lührmann, Reinhard Georg; Gruss, Oliver (PLOS ONE, 2013)
The conserved Prp19 (pre-RNA processing 19) complex is required for pre-mRNA splicing in eukaryotic nuclei. Recent RNAi screens indicated that knockdown of Prp19 complex subunits strongly delays cell proliferation. Here we show that knockdown of the smallest subunit, BCAS2/Spf27, destabilizes the entire complex and leads to specific mitotic defects in human cells. These could result from splicing failures in interphase or reflect a direct function of the complex in open mitosis. Using Xenopus extracts, in which cell cycle progression and spindle formation can be reconstituted in vitro, we tested Prp19 complex functions during a complete cell cycle and directly in open mitosis. Strikingly, immunodepletion of the complex either before or after interphase significantly reduces the number of intact spindles, and increases the percentage of spindles with lower microtubule density and impaired metaphase alignment of chromosomes. Our data identify the Prp19 complex as the first spliceosome subcomplex that directly contributes to mitosis in vertebrates independently of its function in interphase.
Gesehen am 13.07.2021